HYPERTENSIVE PATIENTS AS CANDIDATES FOR RENAL SYMPATHETIC DENERVATION: CONSENSUS OPINION OF HYPERTENSION EXPERTS IN GREECE. (April 2021) - Doumas, Michael; Andreadis, Emmanouil; Davlouros, Periklis; Dimitriadis, Kyriakos; Gkaliagkousi, Eugene; Grassos, Harris; Hatzitolios, Apostolos; Imprialos, Konstantinos; Kalaitzidis, Rigas; Kallistratos, Emmanouil; Konstantinidis, Dimitrios; Kotsis, Vasilios; et al.
Abstract : Objective: Several studies have evaluated the efficacy and safety of renal sympathetic denervation (RSD) in patients with hypertension and other conditions characterized by sympathetic overactivity. However, to date there is no consensus in the literature about which patients are the most appropriate candidates for RSD. This analysis presents the opinions of hypertension experts in Greece regarding potential candidates for RSD. Design and method: Chairpersons of ESH Hypertension Excellence Centers in Greece and their senior clinical research fellows, were invited to participate in a meeting aiming to discuss the current evidence on the clinical utility of RSD. Individual responses were recorded and qualitatively analyzed, in order to reach consensus about potential RSD candidates. Results: Twenty-five experts participated in the meeting (cardiologists 52%, internists 40%, nephrologists 8%). (i) 84% of the experts agreed that patients with resistant or uncontrolled hypertension are the most eligible candidates for RSD. (ii) Patients who are either non-adherent to treatment (72%) or discontinued antihypertensive drugs due to adverse events (64%) were suggested as potential candidates. (iii) Patients with severe left ventricular hypertrophy or other TOD were also proposed as potential candidates (24%). (iv) Individuals with diseases associated with sympathetic overactivity (72%), such as obstructive sleep-apnea syndrome, chronic kidney disease, heart failure, arrhythmias, and polycystic ovary syndrome. (v) Patients at the initial stages of hypertension (12%), women of child-bearing potential (4%), drug naïve patients (16%), and patients of young age without TOD were also considered (12%). (vi) Hypertensive patients with increased sympathetic activity, such as patients with excessive white-coat hypertension or sodium sensitivity, were also proposed as potential candidates (8%). (vii) Patients preferring RSD over life-long drug treatment might also be eligible (24%). Conclusions: Seven patient groups were identified as potential candidates for RSD. Experts agreed on the eligibility of patients with resistant hypertension, yet other groups of patients were also proposed. More data are needed to properly identify those patients who will benefit the most from RSD, aiming towards personalized therapy in this field.